2006
DOI: 10.1680/adcr.2006.18.3.119
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of alkali-activated slag: comparison with ordinary Portland cement

Abstract: A multi-method approach was used for the investigation and comparison of alkali-activated slag binders (AAS), pure slag and ordinary Portland cement (OPC). X-ray fluorescence, X-ray powder diffraction, granulometry, calorimetry, thermo-gravimetric analysis and environmental scanning electron microscope investigations of the microstructure with energy dispersive X-ray analyses were used to characterise the cements and their hydrate phases. In addition, the chemical composition of the pore solution, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
114
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(143 citation statements)
references
References 26 publications
16
114
0
5
Order By: Relevance
“…The concentration of Al is also high in all pore solutions, except the control paste, indicating that Al/Si ratios are considerably higher than that recorded by other researches [29][30][31]. The low Al concentration in the pore solution of the base paste additionally confirms a slow rate of dissolution of slag particles.…”
Section: Pore Solution Chemistrymentioning
confidence: 52%
See 2 more Smart Citations
“…The concentration of Al is also high in all pore solutions, except the control paste, indicating that Al/Si ratios are considerably higher than that recorded by other researches [29][30][31]. The low Al concentration in the pore solution of the base paste additionally confirms a slow rate of dissolution of slag particles.…”
Section: Pore Solution Chemistrymentioning
confidence: 52%
“…7 to Fig 9. Normally the microstructure of AAS paste is dominated by the relatively fast "through solution" precipitation of a gel-like C-S-H matrix in the pore space; and the internal space between the slag grains is readily completely filled with C-S-H gel after 24 hours when stronger activators (sodium silicate, sodium hydroxide) are used [29]. It can be seen that the control paste activated with sodium carbonate shows little hydration at early age (Fig.…”
Section: Semmentioning
confidence: 99%
See 1 more Smart Citation
“…Hummel et al [26] indicated by thermodynamic calculations that HS -is the dominant sulfur species under highly alkaline conditions, which will generate reducing conditions. However, Gruskovnjak et al [27] observed that SO 3 2-may dominate the sulfur speciation under moderately reducing conditions due to kinetic effects, whereas under more strongly reducing conditions, S 2 O 3 2-, HS -and a series of polysulfides will be dominant. The evolution of the speciation of sulfur during slag hydration has been determined by X-ray absorption near-edge structure (XANES) spectroscopy [13,28], where it was observed that the sulfur in an anhydrous granulated blast furnace slag is mainly present in reduced form, S 2-and S 0 , while in the activation of the slag, those sulfur species react with oxygen and alkaline solutions to form S 2 O 3 2-and SO 4 2-.…”
Section: Evolution Of Corrosion Potentialmentioning
confidence: 99%
“…Other authors reported that strength of sodium silicate and sodium hydroxide activated slag increased with the increase in slag fineness [40] up to 6000 cm 2 /g [51]. Gruskovnjak et al [52] used a solid waterglass, solid Nametasilicate pentahydrate (Na 2 SiO 3 .5H 2 O) as a source of activator to activate slag. They reported that the high fineness of the slag represented a further important factor for fast reactivity, in which the small slag particles (< 2μm) were completely hydrated within the first 24 h after mixing, whereas hydration of the larger particles was much slower.…”
Section: Ph Valuesmentioning
confidence: 99%